Confidential Gossip and Organization Studies. Issue 10 (October 2021) - Fan, Ziyun; Grey, Christopher; Kärreman, Dan
This essay sets out the case for regarding confidential gossip as a significant concept in the study of organizations. It develops the more general concept of gossip by combining it with concepts of organizational secrecy in order to propose confidential gossip as a distinctive communicative practice. As a communicative practice, it is to be understood as playing a particular role within the communicative constitution of organizations. That particularity arises from the special nature of any communication regarded as secret, which includes the fact that such communication is liable to be regarded as containing the 'real truth' or 'insider knowledge'. Thus it may be regarded as more than 'just gossip' and also as more significant than formal communication. This role is explored, as well as the methodological and ethical challenges of studying confidential gossip empirically.